RNA-based boronate internucleosidic linkages: an entry into reversible templated ligation and loop formation. Issue 45 (9th November 2018) - Gimenez Molina, Alejandro; Barvik, Ivan; Müller, Sabine; Vasseur, Jean-Jacques; Smietana, Michael
Abstract : The synthesis of a 5′-boronoribonucleotidic phosphoramidite building block has been achieved and incorporated at the 5′ extremities of RNA sequences for the templated assembly of RNA shortmers. Abstract : The use of templates able to control the assembly and disassembly of supramolecular biopolymers is an attractive approach with applications ranging from engineering new biopolymers to the modulation of complex biological systems. Self-assembled nucleic acid-based systems hold thus substantive potential for the construction of well-defined and stimuli-responsive molecular architectures. We report here for the first time the synthesis of a 5′-boronoribonucleotidic phosphoramidite building block, its incorporation at the 5′ extremities of RNA sequences, and its ability to generate boronate internucleosidic linkages by RNA- and DNA-templated ligation. Moreover, melting denaturation studies also revealed that 5′-boronic acid ended RNA sequences are able to promote the formation of RNA loops in the presence of RNA templating partners. Molecular-dynamics (MD) simulations were used to model the structural parameters governing these processes.